Village Level Government Strategy in Increasing Farmers’ Access to Land Tenure as One of The Ways to Accelerate Agrarian Reform In Lemahsubur Village, Tempuran District, Karawang Regency - Aliansyah, Arif; Al Amien, Muhammad Hafidh; Madjid, Nur Kholis; Wahyudi, Riyan Ade; Adrian, Rifqi; Hasan, Fuad; Asyhadi, Farhan (Jurnal Hukum dan Keadilan, 2024)
Lemahsubur Village is one of the villages included in the Tempuran District, Karawang Regency. Agriculture is a very important sector in Indonesia, because Indonesia is an agrarian country and the majority of its population works in the agricultural sector so that agriculture is one of the largest commodities in the village, so the main problem discussed in this article is about the cultivation of agricultural land in Lemahsubur village which is one of the accelerations in the acceleration of agrarian reform. To implement it, the Lemahsubur village government develops the cultivation of the land cultivated by farmers in Lemahsubur village by establishing a farmer group 'Wargi Saluyu' which is a forum for these farmers to be able to manage and develop agricultural land collectively, with the existence of the farmer group, it is hoped that it can accommodate the farmers in Lemahsubur village in land cultivation, with the protection and empowerment of farmers which includes empowerment, financing and funding, supervision, and the role of the community, which is held based on the principles of sovereignty, independence, utility, integration, openness, efficiency, justice, and sustainability. The purpose of writing this article, the author wants to help the community in educating about the land that farmers are working on in Lemahsubur village. This system uses the Forward Chaining method where the process of searching for a forward or forward track. The search process is by providing questions that are the cause of existing problems, especially regarding land, there is a need for consultation to increase manpower in realizing the welfare of Lemahsubur villagers.